Finite Element Analysis of Telecommunication Structure Reinforcement. Issue 4 (14th September 2022) - Fitzalan, Jake; Mashiri, Fidelis
Abstract: Frequent technology upgrades in telecommunications have led to an increase in wind load on the towers that hold this equipment. The legs of lattice towers are critical members to the structure's integrity as they transfer large portions of compressive load through to the foundations. Through the increasing amount of compressive load, these members could eventually fail due to insufficient strength, which has raised the need to reinforce existing structures. Currently within industry, retrofitting new members onto the existing legs is common, however there is currently little research that has been carried out to investigate the effectiveness of these methods. This research investigates the retrofit of a Circular Hollow Section (CHS) that has been strengthened with two steel rods and aims to provide greater clarity on the effectiveness of the design through numerical analysis. This was completed using ABAQUS 2021 by performing both linear and non‐linear buckling analysis. It has been found that the design can improve compressive strength by up to 277.3% for the short column which matches the predicted strength. For the long column, an increase of 130.2% was recorded which is significantly less then calculated values. The results obtained further stress the need for continued research in this field, with an emphasis on experimental results.